Autoantibodies against modified low density Lipoprotein in patients with coronary heart disease and normal individuals - "Mohammadi R; Doosti M; Javadi E; Sarrafnejad A; Karimi A; Mohagheghi A " (Acta Medica Iranica, 2001)
Different classes of autoantibodies against two antigenic forms of modified low density lipoprotein (mod-LDL) were detected in 140 patients by indirect ELISa method. Investigated autoantibodes included total immunoglobulins (IgT). Immunoglobulin G (IgG), and immunoglobulin M (IgM) against oxidized LDL with copper ions (ox-LDL) and modified LDL with malondialdehyde (mal-LDL) (IgT-O) IgT against mal-LDL (IgT-M), IgG against ox-LDL (IgG-O), IgM against ox-LDL (IgM-o), and IgM against mal-LDL (IgM-M) were significantly (P<0.05) higher in patient with coronary atherosclerosis than normal individuals, whereas titer of IgG against mal-LDl (IgG-M) didn’t show any significan difference between these groups. In this study, no correlation was found between autoantibody titers and severity of coronary artery stenosis. The results indicate that titers of these autoantibodies are dependent on an active atherogenic process.